Kompetensi Guru Penggerak dalam Meningkatkan Mutu Pendidikan melalui Implementasi Kurikulum Merdeka di SDN 04 Menanga Semendawai Barat - Syarwani Ahmad; Desiana Desiana; Mahasir Mahasir (CV. Ulil Albab Corp, 2026)
This research aims to analyze and describe the competencies of leading teachers as an effort to improve the quality of education in the implementation of the Merdeka Curriculum at SD Negeri 04 Menanga. The study was conducted at SD Negeri 04 Menanga, located in Menanga Sari Village, Menanga Besar Sub-District, Semendawai Barat District, East Ogan Komering Ulu Regency. The research object focuses on the competencies of leading teachers as a strategic instrument to strengthen educational quality through the application of the Merdeka Curriculum. This research adopts a qualitative approach with a descriptive qualitative method. Primary data sources were obtained from in-depth interviews with the school principal, teachers, and other school community members at SD Negeri 04 Menanga. Meanwhile, secondary data include school documents such as institutional profiles, organizational structures, lists of educators and education personnel, number of students, teacher performance assessments, learning supervision, facilities and infrastructure, as well as teaching schedules. Data collection techniques encompass participatory observation, semi-structured interviews, and document analysis. Data validity is ensured through source and method triangulation. Data analysis is performed qualitatively using typological approaches and SWOT analysis to identify strengths, weaknesses, opportunities, and threats. The research findings indicate that leading teachers at SD Negeri 04 Menanga have successfully implemented the Merdeka Curriculum through student-centered learning, such as differentiated instruction, outdoor activities, and project-based learning. The main supporting factors include support from the government and school stakeholders, while the inhibiting factors encompass resistance from fellow teachers to change and limited digitalization facilities. These findings imply the need for strengthened ongoing training for leading teachers and more adequate resource allocation to optimize educational quality at the elementary school level.